Pelvic chodroma in the left obturator foramen: The first case report. (August 2021) - Swed, Sarya; Dalaleh, Mohammad; Tfankji, Salim; Alhalabi, Nawras; Alyousfi, Rama
Abstract: Introduction and importance: Chondroma is a benign and slow-growing tumour usually located in the hand and foot. Although many cases reported pelvic chondroma, to the best of our knowledge, this case is number one in the world because of the location of the sensitive tumour within the obturator foramen, and we did not review any case mentioned in the medical literature corresponding to our case. Case presentation: A 9-years-old male presented to our hospital, complaining of an inguinal mass, the patient had no history of pelvic discomfort. Computed tomography showed a hard mass in the left inguinal region. By open surgery, we extracted the mass. The patient was discharged after 4 days with no complaints. Clinical discussion: Pelvic chondroma is one of the challenging cases that orthopedist's face. We presented a patient with a very hard, painless, not rubefacient and fixed on palpation mass. Computed tomography is considered an imaging study to evaluate such patients. Most cases of chondroma are treated by performing open surgery to extract the mass. Conclusion: Pelvic chondroma should be extracted by open surgery in order not to extend to nearby tissue and hurt urinary and reproductive organs. The follow-up of these patients is essential, by imaging and pathological studies. Checking family history up is necessary, but in our case, there is no. Highlights: Chondtoma is a benign tumour, it originates in any part of the body. It can be seen in the pelvis, but it is very rare to see it within the obturator foramen, as in our case. Diagnosis is by radiological imagings and histopathology. The optimal measure is surgical treatment by excision of the entire tumour and then follow-up..